Tomography findings in patients confirmed with SARS-CoV-2 and acute respiratory distress syndrome - Córdova-Matamoros, Silvia Dalila; Martínez Padrón, Hadassa Yuef; García-Pérez, Mario Alberto; Villalobos-Silva, José Antonio; Guerrero-Nava, José Miguel; Velandia García, Laura Yesenia (Horizonte Sanitario, 2023)
Objective: Describe the tomographic patterns of lung involvement in patients with SARS-CoV2 and ARDS. Materials and methods: Retrospective, cross-sectional and analytical study. Patients treated at the Regional High Specialty Hospital of Ciudad Victoria "Bicentenario 2010" (HRAEV), with a confirmed diagnosis of COVID-19 by RT-PCR and who had a chest computed tomography performed at the institution in the period from March 1, 2020 to July 31, 2020. A descriptive and analytical analysis was carried out. Results: Tomography studies of 44 patients hospitalized in HRAEV who had ARDS and required IOT were analyzed, of which 72.7% were male, the average age was 64 years, of which 47.7% had Diabetes Mellitus, 63.6% with Systemic Arterial Hypertension and 43.1% with some degree of overweight or obesity. Conclusions: The characteristic tomographic finding of patients with ARDS was a mixed type of ground glass and consolidation with severe and generalized involvement. A high mortality rate was observed in these patients with OTI up to 70%. Keywords: SARS-Cov-2; pattern; ARDS; thorax; Findings.